Evaluating chia (Salvia hispanica L.) seed administration for cholesterol reduction in quail (Coturnix coturnix) - Rahimatul Uthia; Ira Oktaviani Rz; Sri Vina Hidayani; Kustiasih Lestari; Fathul Jannah (Jurnal Ilmiah Pertanian)
Chia (Salvia hispanica L.) seeds contain phenolic compounds such as flavonols and phenolic acids (myricetin, quercetin, kaempferol, caffeic acid) that act as primary and synergistic antioxidants. These antioxidants reduce cholesterol by inhibiting absorption in the intestine and enhancing bile acid formation, facilitating cholesterol excretion through feces. Additionally, the high protein and fiber content in S. hispanica L. seeds reduces appetite and promotes prolonged satiety. This study evaluates the effect of different administration patterns of S. hispanica L. seeds on cholesterol reduction in common quail (Coturnix coturnix). The research involved five groups: three treatment groups receiving S. hispanica L. seeds at varying frequencies (once, twice, three times daily) and two controls (positive, negative), with six C. coturnix in each group. The S. hispanica L. seed dose was 1.8 mg per 200 g body weight (BW) administered for 30 days. Cholesterol levels were measured at baseline and after treatment and analyzed using one-way ANOVA and Duncan’s Post Hoc Test. Results indicated that administering S. hispanica L. seeds three times daily significantly reduced cholesterol levels (p < 0.05) compared to other frequencies. This research provides a foundation for further exploration into practical applications of S. hispanica L. seeds in cholesterol management, both in animals and potentially in humans.